Pengabdian Berbasis Komunitas sebagai Upaya Pencegahan Judi Online pada Remaja melalui Penguatan Etika pergaulan - Afit Datul Musafa’ah; Linda Wati; Muttaqin; Yasirul Amri; Putri Nur Dewi; Indah Agustina; Ahmad Khusairi (khidmatan, 2026)
This study aims to analyze the effectiveness of community-based service as an effort to prevent online gambling in adolescents through strengthening social ethics. The study uses a participatory action research approach that places adolescents as active subjects in problem identification, action planning, educational implementation, and reflection on social changes in their social environment. The subjects of the activity consist of 25 village adolescents who are active in peer groups and potentially exposed to online gambling practices. Data were collected through participatory observation, interviews, documentation, and pretest and posttest evaluations to see changes in knowledge, attitudes, and social control among peers. The results of the study showed that participatory interventions were able to increase adolescents' understanding of the psychological, social, and economic impacts of online gambling and shift their views from considering gambling as entertainment to risky behaviors. Other findings show the emergence of a mechanism of mutual reminder among participants so that peer groups that originally had the potential to be a medium of normalization can turn into a space of social protection. Theoretically, these results confirm that adolescent behavior is strongly influenced by group norms and the quality of social ethics that develop in the community. Thus, PAR-based community-based service contributes as a contextual, participatory, and sustainable prevention model to suppress the influence of the social environment on online gambling behavior in adolescents and strengthen the social resilience of the community in the face of today's contemporary digital exposure.